Effect of Tranquillizer On Weight Gain In Broilers - Santa E George (Department of Pharmacology and Toxicology, College of Veterinary and Animal Sciences, 1978)
A feeding trial of 30 days duration was carried out in 30 days – old commercial broiler chicken to study the effects of two tranquillizers such as meprobamate and nitrazepam incorporated at varying levels in the rations for chicken, on weight gains. There were eight dietary treatments each consisted of 21 birds. The group that had received basal diet without the addition of tranquillizers formed as control while four groups each received basal diet incorporated with meprobamate (Equanil) at levels of 0.2%, 0.4%, 0.6% and 1.2% of the diet and the remaining three groups received diets added with nitrazepam (Hypnotex) at levels of 0.005%, 0.01% and 0.015% respectively. The gain in body weight, feed consumption and haematology of the chicken were recorded and economics of weight gain in the respective treatments worked out. The results of the study indicated that incorporation of tranquillizers in the diet did not promote growth in chicken at a faster rate than the basal diet. Addition of meprobamate in the diet caused mortality in chicken, the maximum had been in groups that received the highest dose levels. There appeared to have a tendency for longer clotting time for the blood in chicken that had received meprobamate and that their liver showed varying degrees of degenerative changes. None of the tranquillizers at any of the levels studied had any effect on the general behaviour of the birds. Based on the results it was concluded that addition of tranquillisers had not produced any beneficial effect in broiler chicken either in promoting a faster growth rate or a savings in feed consumption.